Analisis Puisi “Senja Di Pelabuhan Kecil” Melalui Pendekatan Struktural (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Literary works are arts that have elements of mind, imagination, and emotion. In addition, it is also referred to as creative work that is used as intellectual and emotional consumption. Poetry is a type of literature with language bound by rhythm, rhyme, and the arrangement of stanzas and arrays. Poetry is able to express the emotions and experiences of memorable writers and then poured into a rhyming language style so that it is more interesting to read. The author is interested in analyzing the poem "Dusk in a Small Port" by Chairil Anwar, because the poem is formed with a simple language order but broad meaning. The purpose of this study is to find out the meaning in poetry by Chairil Anwar and to improve the author's understanding of structural approaches. This research method uses a qualitative descriptive method that examines and then describes the meaning of the poem "Dusk in a Small Port" by Chairil Anwar with a structural approach. The structural approach is an approach in literature whose way of working is to analyze the structural elements that build literary works from within, and look for relationships or relationships between elements of one element with another in order to achieve roundness of meaning. based on the analysis of the poem "Dusk in the Small Port", it can be concluded.